Generating political priority for breastfeeding and the adoption of Kenya's 2012 BMS act : the importance of women's leadership - Wamahiu, Maryanne; Baker, Phillip; Dorlach, Tim (Globalization and Health, 2025)
The World Health Organization recommends initiating breastfeeding in the first hour of life, exclusive breastfeeding for six months, and continued breastfeeding for at least two years. Aggressive marketing of breast milk substitutes (BMS) undermines breastfeeding and is linked to adverse child and maternal health outcomes. This is particularly problematic in the Global South, where socioeconomic conditions often amplify the risks associated with BMS. The adoption of national BMS legislation in line with the 1981 International Code of Marketing of Breast-milk Substitutes is therefore crucial but difficult due to strong opposition from the transnational formula milk industry. Breastfeeding advocates in Kenya were able to overcome this powerful opposition when the country adopted a strict BMS Act in 2012, which has since facilitated and protected remarkable improvements in breastfeeding rates. We conduct a qualitative case study to identify the political enablers of the successful adoption of this important law.